Analisis Isi Kecenderungan Pemberitaan Tragedi Kanjuruhan pada Portal Berita di Indonesia - Azqiya, Nizvi Varra; Hadylaya, Michael H; Siregar, Nora Adelinda (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
The Kanjuruhan tragedy captured public attention and media. This article discusses the tendency of framing the Kanjuruhan Tragedy by Indonesian news portals through news searches on Google News.This study uses a quantitative approach with a positivistic paradigm, as well as a content analysis method for news framing categories from Ogbodo et al. (2020). The results of this research show that the Tragedy of Kanjuruhan is not single framed. There are at least 7 (seven) framing related to one event of the Kanjuruhan Tragedy. Indonesian news portals tend to frame news articles about the Kanjuruhan Tragedy in terms of attribution of responsibility. The news analyzed tends to discuss the Indonesian Government's efforts to follow up on the Kanjuruhan Tragedy, as well as reporting developments on the parties involved and responsible for the tragedy.